Training induced changes on physiological and biochemical variables of young indian field hockey players - Manna, I.; Khanna, G. L.; Dhara, P. C. (Biology of Sport, 2009)
The present study aims to find out the training induced changes on different physiological and biochemical parameters in young Indian field hockey players. A total of 30 Indian male field hockey players (age range 14-16 yrs) regularly playing competitive field hockey were selected; a training programme consist of aerobic and anaerobic exercise were followed for 6 wks and 12 wks respectively. Results showed a significant decrease (P<0.05) in body fat, and a significant increase (PO.05) in LBM following both 6 wks and 12 wks of training. Strength of backs and handgrip muscles were also increased significantly (P<0.05) after the training. Significant reduction (PO.05) in heart rates during sub-maximal exercises, maximal exercises and recoveries were noted after both the training programme. Moreover, significant increase (PO.05) in aerobic capacity and anaerobic power were observed after the training. Further, significant reductions (PO.05) were noted in hemoglobin, total cholesterol, triglyceride and LDLC after the training. On the other hand plasma levels of urea, uric acid and HDLC were increased significantly (PO.05) following the training. Present study showed a decrease in body fat and the plasma levels of cholesterol as well as LDLC and increase in HDLC, which is beneficial for good health and better performance. However, reduction in hemoglobin and increase in plasma urea and uric acid may be due to increased training load. Since the data on field hockey players are limited in India, therefore the present study may provide useful information to the coaches to develop their training programme.